Screening of healthcare staff for the prevention of colon cancer - Peteinaris, Angelis; Mulita, Francesk; Bekou, Eleni; Lakiotaki, Dimitra; Kostopoulou, Ira-Eirini; Liolis, Elias; Tatanis, Vasileios; Tasios, Konstantinos; Tchabashvili, Levan; Antzoulas, Andreas; Garantzioti, Vasiliki; Koutras, Antonios; et al. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Malignancies are one of the most important problems of healthcare systems worldwide. Late diagnosis makes the treatment, therapeutic or not, difficult and constitutes an important obstacle to the orderly functioning of the healthcare systems in terms of financial and human resources. The prevention of certain types of cancer offers the general population, through screening tests, the ability to achieve early diagnosis and treatment. The healthcare workforce constitutes a part of the general population that should be aware of the screening tests and the consequences of cancer. Here, we investigated whether healthcare workers in Greek hospitals are well informed about the screening tests used as gold standards for the prevention of colon cancer. Moreover, we studied whether they screen themselves for the prevention of this type of cancer.